Adélie penguins coping with environmental change: results from a natural experiment at the edge of their breeding range - Dugger, Katie M.; Ballard, Grant; Ainley, David G.; Lyver, Phil O'B.; Schine, Casey (Frontiers in Ecology and Evolution, 2014)
We investigated life history responses to extreme variation in physical environmental conditions during a long-term demographic study of Adélie penguins at 3 colonies representing 9% of the world population and the full range of breeding colony sizes. Five years into the 14-year study (1997-2010) two very large icebergs (spanning 1.5 latitude degrees in length) grounded in waters adjacent to breeding colonies, dramatically altering environmental conditions during 2001 - 2005. This natural experiment allowed us to evaluate the relative impacts of expected long-term, but also extreme, short-term climate perturbations on important natural history parameters that can regulate populations. The icebergs presented physical barriers, not just to the penguins but to polynya formation, which profoundly increased foraging effort and movement rates, while reducing breeding propensity and productivity, especially at the smallest colony. We evaluated the effect of a variety of environmental parameters during breeding, molt, migration and wintering periods during years with and without icebergs on penguin breeding productivity, chick mass, and nesting chronology. The icebergs had far more influence on the natural history parameters of penguins than any of the other environmental variables measured, resulting in population level changes to metrics of reproductive performance, including delays in nesting chronology, depressed breeding productivity, and lower chick mass. These effects were strongest at the smallest, southern-most colony, which was most affected by alteration of the Ross Sea Polynya during years the iceberg was present. Additionally, chick mass was negatively correlated with colony size, supporting previous findings indicating density-dependent energetic constraints at the largest colony. Understanding the negative effects of the icebergs on the short-term natural history of Adélie penguins, as well as their response to long-term environmental variation, are important